Kurmuk phonology - Torben Andersen (LibraryPress@UF, 2007)
This article describes the basic aspects of the phonology of Kurmuk, a previously undescribed language belonging to the Northern Burun subbranch of the Western Nilotic family. After a morpho syntactic overview, the treatment of the phonology includes syllable structure and word shapes, vowels and vowel alternation, consonants and consonant alternation, and tones and tonal processes.